2009
DOI: 10.1118/1.3116774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of power spectra for tomosynthesis projections and reconstructed images

Abstract: Burgess et al. ͓Med. Phys. 28, 419-437 ͑2001͔͒ showed that the power spectrum of mammographic breast background follows a power law and that lesion detectability is affected by the power-law exponent ␤ which measures the amount of structure in the background. Following the study of Burgess et al., the authors measured and compared the power-law exponent of mammographic backgrounds in tomosynthesis projections and reconstructed slices to investigate the effect of tomosynthesis imaging on background structure. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 10 publications
8
57
0
Order By: Relevance
“…The exponent b ¼ 3 was calculated based on fractal properties of self-similar objects (such as equal volumes of different sized spheres in the generic phantom above) and is similar to widely reported values. [25][26][27]43 The numerator j carries a dependence on kVp because of the effective attenuation coefficients of object and background, and decreases with scatter as (1=1 þ SPR) 2 . j and hence, anatomical clutter, decrease as a function of increasing kVp (reduced relative contrast).…”
Section: Quantum Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The exponent b ¼ 3 was calculated based on fractal properties of self-similar objects (such as equal volumes of different sized spheres in the generic phantom above) and is similar to widely reported values. [25][26][27]43 The numerator j carries a dependence on kVp because of the effective attenuation coefficients of object and background, and decreases with scatter as (1=1 þ SPR) 2 . j and hence, anatomical clutter, decrease as a function of increasing kVp (reduced relative contrast).…”
Section: Quantum Noisementioning
confidence: 99%
“…The effect of anatomical background on detectability is a subject of considerable interest, commonly modeling the background as power-law noise j=f b included as an additive noise term in the "generalized" NEQ. For example, in breast imaging, the power-law characteristic in 2D mammographic images was characterized by Bochud et al, 21 Burgess, 22,23 and others 24 and extended to 3D breast imaging by Metheany et al, 25 Engstrom et al, 26 Glick et al, 27 Gong et al, 28 and Reiser and Nishikawa, 29 showing b differs in 2D projections versus 3D tomosynthesis and CBCT reconstructions. In a fairly general context, Gang et al 30 showed power-law background noise to arise from superposition of self-similar (fractal) structures in 2D and 3D images, derived relations between b in projection, tomosynthesis, and CBCT, and incorporated the result in a generalized detectability index.…”
Section: Introductionmentioning
confidence: 99%
“…We simulated two types of background images: a simple homogeneous background with linear attenuation set at a 50-50 mix of adipose and glandular tissue and a background with structured noise created by filtering white noise with a power law filter [32,33] f (ν) = κ/ν β , with ν the frequency, β = 3 and κ = 10 −5 mm −1 . The linear attenuation coefficients of this background were rescaled to values between the attenuation of adipose and glandular tissue.…”
Section: E Phantom Simulation and Reconstructionmentioning
confidence: 99%
“…In each mammogram, the region of uniform breast thickness was identified by eroding the skin line and excluding the pectoralis muscle in the MLO views. 10 Square ROIs of 384 pixels side length were extracted, with centers spaced by 200 pixels in each direction. In total, 875 ROIs were extracted from 92 mammograms.…”
Section: Iia Image Datasetmentioning
confidence: 99%
“…2 Power-law backgrounds have been widely used as a statistical model for breast backgrounds, [3][4][5][6][7][8][9] and power-law exponents in clinical tomosynthesis and breast CT images have been investigated. 10,11 To date, power-law coefficients have been estimated from the radial averaged of the power spectrum. However, we have observed that, in general, breast structure in a mammographic ROI is oriented and therefore the corresponding periodogram does not exhibit radial symmetry.…”
Section: Introductionmentioning
confidence: 99%